Metformin anticipates peak of lactate during high-intensity interval training but no changes performance or neuromuscular response in amateur swimmers - Norberto, Matheus Silva; De Arruda, Tarine Botta; Cursiol, Jonatas Augusto; De Andrade, Vitor Luiz [UNESP]; De Araujo, Gustavo Gomes; Papoti, Marcelo (Elsevier, 2021)
Background & aims: Metformin demonstrated potential to improve metabolic efficiency in short-intense and prolonged-continuous efforts. The present study investigates the acute effects of metformin intake on performance, rating of perceived exertion (RPE), blood lactate, blood glucose and neuromuscular parameters related to swimming high-intensity interval series. Methods: A double-blind, crossover, randomized and placebo-controlled study was carried out. Seven healthy swimmers ingested metformin (500 mg) or placebo capsules on different days and performed a typical high-intensity training series (10 bouts of 50 m with a 3-min interval). Performance, RPE, neuromuscular parameters (lower and upper limbs), blood lactate and glucose were analyzed by the Wilcoxon Signed-Rank and Friedman's tests between supplementation situations and moments, respectively (p > 0.05), the moment where glucose and blood lactate peak were found were analyzed by a Student t-test (p > 0.05) and a Bayesian repeated-measures ANOVA for effects analysis (BFincl). Results: The anticipation of blood glucose and peak lactate was signaling by the interaction effect (metformin increased and placebo decreased) between the eighth and the last bout (BFincl: 4.230 and 5.188 respectively). The second interaction effect of blood glucose and lactate (metformin maintained and placebo increased) during recoveries between 5 min and 7 min (BFincl: 3.825 and 3.806 respectively) also signaling the anticipatory behavior of both physiological parameters. The anticipation of blood lactate peak concentration after metformin intake confirms the anticipatory behavior of blood lactate (p: 0.015). Conclusions: The anticipatory behavior of glucose was not confirmed. Although the anticipatory peak of blood lactate, metformin does not affect neuromuscular responses, RPE and performance. Registration of clinical trial: RBR-67wxdw8 Effects of metformin during swimmer training performance.
Keywords: Blood glucose; Blood lactate; Neuromuscular fatigue; Swimming; Typical series performance